(untitled) (Pokhara Engineering College Journal, 2025)
This paper comprehensively reviews analytical approaches for designing welded connections based on established design standards, including European, US, and Indian standards. The study emphasizes the behaviour of fillet welds under various load directions, demonstrating that their strength depends significantly on the orientation of the applied forces. Through detailed analysis of design guidelines and independent research, this review highlights the directional and mean stress methods in European standards, the Load and Resistance Factor Design (LRFD) and Allowable Stress Design (ASD) in US standards and Indian standards. The findings offer a comparative perspective on welded connections’ load-bearing capacity and resistance factors, providing valuable insights such as guidance on selecting standards based on loading conditions and material strength considerations for safer and cost-effective welded connections.